2022
DOI: 10.1523/jneurosci.1914-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Inactivation of Sodium Channels as a Mechanism of Adaptation in CA1 Pyramidal Neurons

Abstract: Many hippocampal CA1 pyramidal cells function as place cells, increasing their firing rate when a specific place field is traversed. The dependence of CA1 place cell firing on position within the place field is asymmetric. We investigated the source of this asymmetry by injecting triangular depolarizing current ramps to approximate the spatially-tuned, temporally-diffuse depolarizing synaptic input received by these neurons while traversing a place field. Ramps were applied to CA1 pyramidal neurons from male r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(19 citation statements)
references
References 64 publications
(92 reference statements)
1
10
0
Order By: Relevance
“…The cascade of events that follow cholinergic activation in these neurons includes the suppression of a number of outward currents (Brown and Adams, 1980; Hoffman and Johnston, 1998; Buchanan et al, 2010; Giessel and Sabatini, 2010) some of which are also involved in firing rate adaptation (Stocker et al, 1999; Gu et al, 2005; Pedarzani et al, 2005; Otto, 2006; Chen et al, 2014). We have previously examined the contribution of small-conductance calcium-activated potassium (SK) current, M-type potassium current, and A-type potassium current with respect to the asymmetric firing in response to symmetric current ramps (Upchurch et al, 2022). We found that, in the relatively low range of firing frequencies evoked by this type of stimulation, the adaptation induced by these currents does not play a role in shifting action potentials to earlier times during the ramp.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The cascade of events that follow cholinergic activation in these neurons includes the suppression of a number of outward currents (Brown and Adams, 1980; Hoffman and Johnston, 1998; Buchanan et al, 2010; Giessel and Sabatini, 2010) some of which are also involved in firing rate adaptation (Stocker et al, 1999; Gu et al, 2005; Pedarzani et al, 2005; Otto, 2006; Chen et al, 2014). We have previously examined the contribution of small-conductance calcium-activated potassium (SK) current, M-type potassium current, and A-type potassium current with respect to the asymmetric firing in response to symmetric current ramps (Upchurch et al, 2022). We found that, in the relatively low range of firing frequencies evoked by this type of stimulation, the adaptation induced by these currents does not play a role in shifting action potentials to earlier times during the ramp.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7A2, 7B2, and 7C2 show the nanomolar [Ca 2+ ] increases in the outer shell, both in the simulated control and CCh conditions. Note that in control (A2) and with high IP 3 but no nanodomain (C2), the Ca 2+ concentration in the outer shell begins to decrease prior to cessation of spiking (see red arrows), due to the decrease in frequency during the down-ramp because of the Na + channel long-term inactivation (Upchurch et al, 2022). Figure 7A3 shows no noticeable micromolar increase in Ca 2+ concentration in the nanodomain under control conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations